Modified epoxy resin and coating composition
Patent Information
- Application Number
- JP2021000946
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-06
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2041-01-06
AI Technical Summary
【0010】 本発明によれば、密着耐久性を有する塗膜を形成可能な変性エポキシ樹脂及び塗料組成物が提供される。
Smart Images

Figure 0007644473000001 
Figure 0007644473000002 
Figure 0007644473000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a modified epoxy resin and a coating composition. More specifically, the present invention relates to a modified epoxy resin and a coating composition capable of forming a coating film having excellent adhesion durability. [Background technology]
[0002] Conventionally, a coating film has been formed on the surface of a substrate to be coated, such as a steel plate, in order to impart rust-preventive properties to the surface. In forming a coating film, a coating film of an undercoat paint (primer) may be formed on the substrate, and a coating film of a topcoat paint or an intermediate paint may be formed on the undercoat paint. Various resins have been investigated for use in these coating films, and epoxy resins, in particular, are often used as materials for resin compositions for primers because of their excellent adhesion.
[0003] For example, Patent Document 1 discloses that a modified epoxy resin obtained by reacting a bisphenol-type epoxy resin with a given amount of a specific aliphatic amine and a given amount of another amine has excellent solubility in solvents and is suitable for a coating material having excellent drying properties, corrosion resistance, and water resistance.
[0004] Furthermore, Patent Document 2 discloses that a paint binder containing a modified epoxy resin having a predetermined amine value, which is obtained by reacting an amine-modified epoxy resin, which is a reaction product of a bisphenol-type epoxy resin and amines, with a dicarboxylic acid, exhibits excellent adhesion to non-ferrous alloys. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 11-100431 [Patent Document 2] JP 2001-164180 A Summary of the Invention [Problem to be solved by the invention]
[0006] The adhesion of the coating film is a basic performance for exerting the rust-preventive protective ability of the coated substrate. Furthermore, considering that the article made of the substrate is exposed to multiple external factors during use, in order to effectively exert the rust-preventive protective ability, it is desired that the coating film not only has excellent adhesion, but also has the ability to sufficiently maintain adhesion against each of the external factors. However, the anti-rust paints so far have not maintained adhesion sufficient to sufficiently resist multiple external factors. For example, the coating film according to the technology shown in Patent Document 1 peels off from the cracks when it is subjected to impact, and is unable to maintain adhesion. In addition, the coating film according to the technology shown in Patent Document 2 is unable to sufficiently maintain adhesion against immersion in water and salt water.
[0007] Therefore, an object of the present invention is to provide a modified epoxy resin and a coating composition capable of forming a coating film having the property of maintaining excellent adhesion even when subjected to an impact and when exposed to water immersion and / or salt water (hereinafter, this property is also referred to as "adhesion durability"). [Means for solving the problem]
[0008] As a result of intensive research, the present inventors have found that a modified epoxy resin obtained by reacting a solid epoxy resin, a liquid epoxy compound, an amine, and a polycarboxylic acid, and a resin composition using the modified epoxy resin, can form a coating film with excellent adhesion retention. The present invention was completed through further research based on this finding.
[0009] That is, the present invention provides the following aspects. Item 1. A modified epoxy resin having a molecular structure obtained by reacting (a1) a solid epoxy resin, (a2) a liquid epoxy compound, (b) an amine, and (c) a polycarboxylic acid. Item 2. The modified epoxy resin according to Item 1, wherein the epoxy equivalent of the component (a1) is 430 or more. Item 3. The modified epoxy resin according to Item 1 or 2, wherein the epoxy equivalent of the component (a2) is 330 or less. Item 4. The modified epoxy resin according to any one of Items 1 to 3, wherein the component (a2) is a bisphenol-type epoxy resin. Item 5. The modified epoxy resin according to any one of Items 1 to 3, wherein the component (a2) is a polyol polyglycidyl ether. Item 6. The modified epoxy resin according to any one of Items 1 to 5, wherein the amount of the (a2) component is 2 to 180 parts by mass per 100 parts by mass of the (a1) component. Item 7. The modified epoxy resin according to any one of Items 1 to 6, wherein the component (b) contains a primary amine and a secondary amine. Item 8. The modified epoxy resin according to Item 7, wherein the primary amine is an aliphatic amine. Item 9. The modified epoxy resin according to Item 8, wherein the aliphatic amine has 8 or more carbon atoms. Item 10. The modified epoxy resin according to any one of Items 7 to 9, wherein a molar ratio of the secondary amine to the primary amine is 0.3 to 10. Item 11. The modified epoxy resin according to any one of Items 1 to 10, wherein the component (c) is an aliphatic polycarboxylic acid. Item 12. The modified epoxy resin according to Item 11, wherein the aliphatic polycarboxylic acid has 8 or more carbon atoms. Item 13. The modified epoxy resin according to any one of Items 1 to 12, wherein the molar ratio of amino group hydrogen atoms to epoxy groups is 0.2 or more. Item 14. The modified epoxy resin according to any one of Items 1 to 13, wherein a molar ratio of carboxyl groups to epoxy groups is 0.8 or less. Item 15. A coating composition comprising (I) a modified epoxy resin according to any one of items 1 to 14. Item 16. The coating composition according to item 15, further comprising (II) an anti-rust pigment. Item 17. The coating composition according to Item 16, wherein the component (II) is selected from the group consisting of phosphate compounds, molybdate compounds, and zinc salt compounds, alkaline earth metal salt compounds, and bismuth compounds other than the phosphate compounds and the molybdate compounds. Item 18. The coating composition according to Item 16 or 17, wherein the blending amount of the component (II) is 25 to 125 parts by mass per 100 parts by mass of the component (I). Item 19. The coating composition according to any one of Items 15 to 18, further comprising (III) an epoxy-functional alkoxysilane. Item 20. The coating composition according to Item 19, wherein the blending amount of the component (III) is more than 0 part by mass and not more than 24 parts by mass per 100 parts by mass of the component (I). Item 21. A laminate comprising a metal substrate and a coating film of the coating composition according to any one of Items 15 to 20 provided on the metal substrate. Item 22. The laminate according to Item 21, wherein the material of the metal substrate is selected from the group consisting of iron, aluminum, and stainless steel. Item 23. An article comprising the laminate according to item 21 or 22. Effect of the Invention
[0010] According to the present invention, there are provided a modified epoxy resin and a coating composition capable of forming a coating film having adhesion durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] 1. Modified epoxy resin The modified epoxy resin of the present invention is characterized by having a molecular structure obtained by reacting (a1) a solid epoxy resin (hereinafter also referred to as "component (a1)"), (a2) a liquid epoxy compound (hereinafter also referred to as "component (a2)"), (b) an amine (hereinafter also referred to as "component (b)"), and (c) a polyvalent carboxylic acid (hereinafter also referred to as "component (c)"). In other words, the epoxy resin of the present invention is characterized by having a molecular structure in which a polymer of components (a1) and (a2) is modified with components (b) and (c). The modified epoxy resin of the present invention will be described in detail below.
[0012] Hereinafter, the "adhesion durability" of a coating film refers to the property of a coating film provided on a metal substrate (particularly, cold-rolled steel sheet and galvanized steel sheet) that allows the coating film to maintain excellent adhesion to the metal substrate both when an impact is applied and when the coating film is submerged in water and / or exposed to salt water. Furthermore, the term "adhesion durability of the coating film against salt water" refers to the adhesion durability of the coating film against salt water among the above-mentioned "adhesion durability", and the term "adhesion durability of the coating film against impact" refers to the adhesion durability of the coating film against impact among the above-mentioned "adhesion durability". The term "flex resistance" of a coating film refers to the property of being able to suppress the occurrence of cracks when the coating film is bent. The term "crack resistance" of a coating film refers to the property of being able to suppress the occurrence of cracks when an impact is applied to the coating film.
[0013] In this specification, the numerical ranges indicated with "to" include both ends of the range. For example, the expression "30 to 200 nm" means that the range is from 30 nm to 200 nm.
[0014] 1-1.(a1) Solid epoxy resin The solid epoxy resin, which is the component (a1), is an epoxy resin that maintains a solid state at room temperature (specifically, 25°C). In the present invention, the solid state refers to a state that does not exhibit fluidity and gel properties at the above-mentioned room temperature, and excludes liquid and semi-solid states that exhibit fluidity and / or gel properties at the above-mentioned room temperature. Specifically, the solid state refers to a hardness of 5N or more at 25°C. The hardness here refers to a value measured using a rheometer manufactured by Rheotec Co., Ltd., with a pressure-sensitive axis of 5φ, a penetration speed of 2cm / min, and a penetration depth of 3mm. In the present invention, the epoxy resin refers to a compound containing two or more epoxy groups in the molecule.
[0015] The type of solid epoxy resin is not particularly limited, and examples thereof include bisphenol-type epoxy resins; biphenyl-type epoxy resins; alicyclic epoxy resins; polyfunctional glycidyl amine resins such as tetraglycidylaminodiphenylmethane; polyfunctional glycidyl ethers such as tetraphenylglycidyl ether ethane; phenol novolac-type epoxy resins and cresol novolac-type epoxy resins; reaction products of epichlorohydrin with a polyphenol compound obtained by a condensation reaction of a phenolic compound such as phenol, o-cresol, m-cresol, naphthol, or the like with an aromatic aldehyde having a phenolic hydroxyl group; reaction products of epichlorohydrin with a polyphenol compound obtained by an addition reaction of a phenolic compound with a diolefin compound such as divinylbenzene or dicyclopentadiene; epoxidation products of a ring-opening polymer of 4-vinylcyclohexene-1-oxide with a peracid; and epoxy resins having a heterocycle such as triglycidyl isocyanurate.
[0016] Among these solid epoxy resins, from the viewpoint of further increasing the adhesion durability of the coating film, preferably, bisphenol type epoxy resins, specifically, bisphenol A type epoxy resins (i.e., polycondensates of bisphenol A and epihalohydrin) and bisphenol F type epoxy resins (i.e., polycondensates of bisphenol F and epihalohydrin), more preferably, bisphenol A type epoxy resins are used. Specific examples include compounds represented by the following formula (1). In formula (1), R are each independently a hydrogen atom or a methyl group, and n is a number of 1.8 or more.
[0017] [ka]
[0018] The number average molecular weight of the component (a1) (polystyrene equivalent molecular weight obtained by gel permeation chromatography (GPC) measurement) is not particularly limited as long as it imparts solid properties, but may be, for example, 900 or more.
[0019] The epoxy equivalent of component (a1) is not particularly limited as long as it provides solid properties, but from the viewpoint of improving the adhesion durability of the coating film, it can be, for example, 430 or more, preferably 440 or more, and more preferably 470 or more. From the viewpoint of further improving the adhesion durability of the coating film and imparting excellent flex resistance to the coating film, the epoxy equivalent of component (a1) is even more preferably 590 or more, and even more preferably 650 or more. From the viewpoint of further improving the adhesion durability of the coating film to salt water in particular, the epoxy equivalent of component (a1) is particularly preferably 790 or more, and most preferably 840 or more.
[0020] The upper limit of the range of the epoxy equivalent of the (a1) component is not particularly limited, but from the viewpoint of improving the adhesion durability of the coating film and imparting excellent bending resistance to the coating film, it is, for example, 4200 or less, preferably 3800 or less. Furthermore, from the viewpoint of imparting crack resistance to impact to the coating film and further improving the adhesion durability of the coating film and / or further increasing the bending resistance of the coating film, the epoxy equivalent of the (a1) component is more preferably 2100 or less, and even more preferably 1900 or less. Furthermore, from the viewpoint of further increasing the crack resistance of the coating film against impact and / or further increasing the adhesion durability of the coating film against salt water, the epoxy equivalent of the (a1) component is more preferably 1010 or less, and particularly preferably 960 or less.
[0021] Commercially available products that can be used as the component (a1) include bisphenol A type epoxy resins such as jER1001, jER1002, jER1003, jER1003F, jER1004, jER1004FS, jER1004F, jER1004AF, jER1055, jER1005F, jER1006FS, jER1007, jER1007FS, jER1008, and jER1009 (all manufactured by Mitsubishi Chemical Corporation), Epotohto YD-011, Epotohto YD-012, Epotohto YD-013, Epotohto YD-014, Epotohto YD-017, Epotohto YD-019, and Epotohto YD-020. G (all manufactured by Nippon Steel Chemical & Material Co., Ltd.), EPICLON 1050, EPICLON 3050, EPICLON 4050, EPICLON 7050 (all manufactured by DIC Corporation), DER-661, DER-663U, DER-664, DER-667, DER-668, DER-669 (all manufactured by The Dow Chemical Company); and bisphenol F type epoxy resins include Epotohto YDF-2001, Epotohto YDF-2004, Epotohto YDF-2005RD (all manufactured by Nippon Steel & Sumitomo Metal Corporation), jER4004P, jER4005P, jER4007P (all manufactured by Mitsubishi Chemical Corporation).
[0022] The ratio of the (a1) component to 100 parts by mass of the total amount of the components constituting the modified epoxy resin is not particularly limited, but from the viewpoint of further improving the adhesion durability, for example, the ratio is 25 to 95 parts by mass, preferably 60 to 93 parts by mass, and more preferably 79 to 90 parts by mass.
[0023] 1-2.(a2) Liquid epoxy compounds The liquid epoxy compound, which is component (a2), is an epoxy resin that maintains a liquid state at room temperature (specifically, 25°C). In the present invention, the term "liquid" refers to a state that exhibits fluidity at the above-mentioned room temperature, and preferably refers to a low viscosity of 20 Pa·s or less, preferably 10 Pa·s or less, at the above-mentioned room temperature. In the present invention, the liquid epoxy compound refers to a compound that contains an epoxy group in the molecule, and specifically includes both a liquid compound that contains two or more epoxy groups in the molecule (i.e., a liquid epoxy resin) and a liquid compound that contains one epoxy group in the molecule (i.e., a compound that can be generally used as a reactive diluent), and either one of these may be used, or both may be used in combination.
[0024] The type of liquid epoxy resin is not particularly limited, and examples thereof include bisphenol-type epoxy resins; biphenyl-type epoxy resins; alicyclic epoxy resins; polyfunctional glycidylamine resins such as tetraglycidylaminodiphenylmethane; polyfunctional glycidyl ethers such as polyol polyglycidyl ether; phenol novolac-type epoxy resins and cresol novolac-type epoxy resins; reaction products of epichlorohydrin with a polyphenol compound obtained by a condensation reaction of a phenolic compound such as phenol, o-cresol, m-cresol, naphthol, or the like with an aromatic aldehyde having a phenolic hydroxyl group; reaction products of epichlorohydrin with a polyphenol compound obtained by an addition reaction of a phenolic compound with a diolefin compound such as divinylbenzene or dicyclopentadiene; epoxidation products of a ring-opening polymer of 4-vinylcyclohexene-1-oxide with a peracid; and epoxy resins having a heterocycle such as triglycidyl isocyanurate.
[0025] Among the above-mentioned liquid epoxy resins, specific examples of bisphenol-type epoxy resins include compounds represented by formula (1) shown in the above "(a1) Solid epoxy resin" in which R is independently a hydrogen atom or a methyl group and n is a number less than 0.7.
[0026] Among the above-mentioned liquid epoxy resins, the number average molecular weight of the polymer (polystyrene equivalent molecular weight obtained by gel permeation chromatography (GPC) measurement) is not particularly limited as long as it gives liquid properties, and examples thereof include 600 or less.
[0027] Among the examples of the liquid epoxy resin, polyol polyglycidyl ether is an ether of a polyol and two or more glycidyl alcohols. Examples of the polyol include aliphatic polyols having 2 to 30 carbon atoms, preferably 2 to 22 carbon atoms, such as ethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, trimethylolpropane, glycerol, polyglycerol, pentaerythritol, and sorbitol. Specific examples of polyol polyglycidyl ethers include ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane polyglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, and sorbitol polyglycidyl ether.
[0028] These liquid epoxy resins may be used alone or in combination of two or more kinds.
[0029] Examples of liquid compounds containing one epoxy group in the molecule include monofunctional glycidyl ether resins, specifically higher alcohol glycidyl ethers (specifically, having 6 or more carbon atoms, preferably 8 or more, more preferably 10 or more carbon atoms). These liquid compounds containing one epoxy group in the molecule may be used alone or in combination.
[0030] Among these liquid epoxy compounds, from the viewpoint of further enhancing the adhesion durability of the coating film, preferred are liquid epoxy resins, more preferred are (a21) bisphenol-type epoxy resins (hereinafter also referred to as "component (a21)") and polyfunctional glycidyl ethers, more preferred are polyfunctional glycidyl ethers, even more preferred are (a22) polyol polyglycidyl ethers (hereinafter also referred to as "component (a22)"), and even more preferred are ethers of polyol and two glycidyl alcohols (i.e., polyol diglycidyl ethers).
[0031] The epoxy equivalent of the (a2) component is not particularly limited as long as it provides liquid properties, but from the viewpoint of improving the adhesion durability of the coating film, it can be, for example, 330 or less. In particular, the epoxy equivalent of the (a22) component is preferably 300 or less, more preferably 280 or less, and even more preferably 220 or less, from the viewpoint of improving the adhesion durability of the coating film, and the epoxy equivalent of the (a21) component is preferably 200 or less, from the viewpoint of improving the adhesion durability of the coating film. In particular, from the viewpoint of further improving the adhesion durability of the coating film to salt water, the epoxy equivalent of the (a2) component is more preferably 165 or less, and even more preferably 150 or less. The lower limit of the range of the epoxy equivalent of the (a2) component is not particularly limited, but can be, for example, 100 or more, preferably 120 or more.
[0032] Commercially available products that can be used as component (a2) include commercially available bisphenol A type epoxy resins such as jER827, jER828, jER828EL, jER828XA, and jER834 (all manufactured by Mitsubishi Chemical Corporation), Epotohto YD-115, Epotohto YD-115G, Epotohto YD-115CA, Epotohto YD-118T, Epotohto YD-127, Epotohto YD-128, Epotohto YD-128G, and Epotohto YD-128S (all manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.), EPICLON840, EPICLON840-S, and EPICLON8 Examples of commercially available bisphenol F type epoxy resins include jER806, jER806H, jER807 (all manufactured by Mitsubishi Chemical Corporation); examples of polyol polyglycidyl ethers include Epolight 40E, Epolight 100E, Epolight 200E, Epolight 400E, Epolight 70P, Epolight 200P, Epolight 400P, Epolight 1500NP, Epolight 1600, Epolight 80MF, Epolight 100MF (all manufactured by Kyoeisha Chemical Co., Ltd.).
[0033] The amount of the (a2) component per 100 parts by mass of the (a1) component is not particularly limited, but from the viewpoint of improving adhesion durability, the amount is, for example, 2 to 180 parts by mass, preferably 2.7 to 100 parts by mass, more preferably 4 to 40 parts by mass, even more preferably 5 to 8 parts by mass, and even more preferably 5.5 to 7 parts by mass, or 5.7 to 6.5 parts by mass.
[0034] The ratio of the total amount of the (a1) component and the (a2) component to 100 parts by mass of the total amount of the components constituting the modified epoxy resin is not particularly limited, but from the viewpoint of further improving the adhesion durability, for example, the ratio is 74 to 97 parts by mass, preferably 80 to 95 parts by mass, and more preferably 85 to 93 parts by mass.
[0035] 1-3.(b)Amine Examples of the amine as component (b) are not particularly limited, and include, for example, primary amines and secondary amines. Examples of other types of amines include monoamines and diamines (compounds in which an amino group is bonded to each of two different carbon atoms). Examples of still other types of amines include aliphatic (non-cyclic aliphatic) amines, alicyclic (cyclic aliphatic) amines, aromatic amines, and more specifically, aliphatic amines with 1 or more carbon atoms, alicyclic amines with 5 or more carbon atoms, and aromatic amines with 6 or more carbon atoms.
[0036] Specific examples of the amine include primary amines such as aliphatic monoamines having one or more carbon atoms, such as ethylamine, propylamine, butylamine, hexylamine, octylamine, laurylamine, stearylamine, palmitylamine, oleylamine, and 2-ethylhexylamine; alicyclic monoamines having five or more carbon atoms, such as cyclopentylamine, cyclohexylamine, and norbornylamine; aliphatic diamines having two or more carbon atoms, such as ethylenediamine, propylenediamine, hexamethylenediamine, 2,2,4-trimethylhexanediamine, and 2,4,4-trimethylhexanediamine; alicyclic diamines having five or more carbon atoms, such as isophoronediamine; and aromatic amines having six or more carbon atoms, such as toluidine, xylidine, cumidine (isopropylaniline), hexylaniline, nonylaniline, dodecylaniline, benzylamine, and phenethylamine. Examples of secondary amines include secondary aliphatic monoamines having two or more carbon atoms, such as diethylamine, dipropylamine, and dibutylamine. These amines may be used alone or in combination of two or more.
[0037] Among these amines, from the viewpoint of improving adhesion durability, preferably, a combination of a primary amine and a secondary amine is used as the component (b), more preferably, both the primary amine and the secondary amine are monoamines, and even more preferably, the primary amine is an aliphatic amine (aliphatic monoamine), and from the viewpoint of further improving adhesion durability of the coating film to salt water, the carbon number of the aliphatic amine is preferably 8 or more. The upper limit of the carbon number range of the aliphatic amine is not particularly limited, but may be, for example, 22 or less, preferably 12 or less. The upper limit of the carbon number range of the secondary amine is not particularly limited, but may be, for example, 24 or less, preferably 16 or less, and even more preferably 10 or less.
[0038] When a combination of a primary amine and a secondary amine is used as component (b), the molar ratio of the secondary amine to the primary amine (moles of secondary amine / moles of primary amine) is not particularly limited, but from the viewpoint of improving the adhesion durability of the coating film, it is, for example, 0.3 to 10, preferably 0.5 to 8, and from the viewpoint of further improving the adhesion durability of the coating film particularly to salt water, it is more preferably 0.7 to 5, even more preferably 0.9 to 3, and even more preferably 1 to 2.
[0039] The molar ratio of amino group hydrogen atoms to epoxy groups of the modified epoxy resin (moles of amino group hydrogen atoms / moles of epoxy groups) is not particularly limited, but from the viewpoint of increasing the adhesion durability of the coating film, it is, for example, 0.2 or more, preferably 0.4 or more, more preferably 0.6 or more, and from the viewpoint of increasing the adhesion durability of the coating film as well as the bending resistance, it is even more preferably 0.7 or more, and even more preferably 0.75 or more. The upper limit of the molar ratio range of amino group hydrogen atoms to epoxy groups of the modified epoxy resin is not particularly limited, but from the viewpoint of increasing the adhesion durability, it is, for example, 1 or less, preferably 0.95 or less, and from the viewpoint of further increasing the adhesion durability of the coating film to salt water, it is more preferably 0.9 or less, more preferably 0.85 or less, and even more preferably 0.8 or less. The amino group hydrogen atoms refer to hydrogen atoms constituting an amino group, and for example, 2 moles of hydrogen atoms constituting 1 mole of a primary amino group (-NH2) and 1 mole of hydrogen atoms constituting 1 mole of a secondary amino group (-NHR).
[0040] 1-4.(c) Polycarboxylic acids Examples of the polycarboxylic acid which is the component (c) are not particularly limited, and include, for example, an aliphatic polycarboxylic acid, an alicyclic polycarboxylic acid, and an aromatic polycarboxylic acid.
[0041] Examples of the aliphatic polycarboxylic acid include aliphatic polycarboxylic acids having 2 or more carbon atoms, such as oxalic acid, malonic acid, succinic acid, maleic acid, itaconic acid, glutaric acid, adipic acid, pimelic acid, 2,2-dimethylglutaric acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, and 1,3,6-hexanetricarboxylic acid; examples of the alicyclic polycarboxylic acid include alicyclic polycarboxylic acids having 7 or more carbon atoms, such as 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid; examples of the aromatic polycarboxylic acid include terephthalic acid, isophthalic acid, phthalic acid, diphenic acid, naphthalic acid, 1,2-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, aromatic tetracarboxylic acids such as hemimellitic acid, trimellitic acid, trimellitic anhydride, and pyromellitic acid, and aromatic polycarboxylic acids having 8 or more carbon atoms, such as mellitic acid. These polyvalent carboxylic acids may be used alone or in combination of two or more.
[0042] Among these polyvalent carboxylic acids, from the viewpoint of improving the adhesion of the coating film, preferred are aliphatic polyfunctional carboxylic acids and alicyclic polyfunctional carboxylic acids. Furthermore, from the viewpoint of further improving the adhesion durability of the coating film, particularly adhesion durability against impact and / or salt water, and / or from the viewpoint of improving the bending resistance of the coating film, more preferred are aliphatic polyfunctional carboxylic acids, and even more preferred are aliphatic dicarboxylic acids. Furthermore, from the viewpoint of further improving the adhesion durability of the coating film, particularly against impact and / or salt water, more preferred are aliphatic polyfunctional carboxylic acids having 8 or more carbon atoms, and even more preferred are aliphatic dicarboxylic acids having 8 or more carbon atoms.
[0043] The molar ratio of the carboxyl group to the epoxy group of the modified epoxy resin (moles of the carboxyl group / moles of the epoxy group) is not particularly limited, but from the viewpoint of increasing the adhesion durability of the coating film, it is, for example, 0.8 or less, preferably 0.6 or less, more preferably 0.5 or less, and even more preferably 0.4 or less, and from the viewpoint of increasing the adhesion durability of the coating film as well as the bending resistance, it is more preferably 0.3 or less, and even more preferably 0.23 or less. The upper limit of the molar ratio range of the carboxyl group to the epoxy group of the modified epoxy resin is not particularly limited, but from the viewpoint of increasing the adhesion durability, it is, for example, 0.05 or more, preferably 0.09 or more, and from the viewpoint of further increasing the adhesion durability of the coating film to salt water, it is more preferably 0.14 or more, and even more preferably 0.18 or more.
[0044] 1-5. Synthesis of modified epoxy resin The method for synthesizing the modified epoxy resin is not particularly limited as long as the above-mentioned components (a1) and (a2) are polymerized and modified with the components (b) and (c). A known epoxy resin polymerization step, an amine modification step, and an acid modification step may be arbitrarily combined.
[0045] In particular, from the viewpoint of enhancing adhesion durability, the above-mentioned modified epoxy resin synthesis method is preferably carried out by first polymerizing the above-mentioned (a1) component and the above-mentioned (a2) component and modifying them with the (b) component, and then modifying them with the (c) component. In this case, more specifically, in a reaction solution containing the (a1), (a2) and (b) components in a solvent, the reaction is carried out at a temperature of preferably 90 to 130°C, more preferably 100 to 120°C, and then the (c) component is added to the reaction solution and the reaction is carried out at a temperature of preferably 110 to 140°C, more preferably 120 to 130°C, to synthesize the modified epoxy resin.
[0046] The solvent used in the synthesis of the modified epoxy resin is not particularly limited, and examples thereof include alcohol solvents such as methanol, ethanol, N-propanol, isopropanol, ethylene glycol, and propylene glycol; terpene solvents such as α- or β-terpineol; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, and N-methyl-2-pyrrolidone; aromatic hydrocarbon solvents such as toluene, xylene, and tetramethylbenzene; cellosolve, methyl cellosolve, ethyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, ethyl carbitol, butyl carbitol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, diphenyl ether, propylene glycol monoethyl ether, diphenyl ether, propylene glycol monomethyl ether, diphenyl ... Examples of the solvent include glycol ether solvents such as propylene glycol monomethyl ether, dipropylene glycol monoethyl ether, triethylene glycol monomethyl ether, and triethylene glycol monoethyl ether; and acetate ester solvents such as ethyl acetate, n-butyl acetate, isobutyl acetate, sec-butyl acetate, tert-butyl acetate, cellosolve acetate, ethyl cellosolve acetate, butyl cellosolve acetate, carbitol acetate, ethyl carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and 3-methoxy-3-methylbutyl acetate.
[0047] 1-6.Applications The modified epoxy resin of the present invention can form a coating film having excellent adhesion durability. Specifically, the modified epoxy resin of the present invention has an excellent property of maintaining a state of adhesion to the metal substrate when the coating film is applied as a coating film on a metal substrate (particularly, an iron substrate such as a cold-rolled steel sheet or a galvanized steel sheet) and is subjected to external stimuli such as impact, water immersion, and / or salt water. Therefore, the epoxy resin of the present invention can be used as an active ingredient of a coating composition to be applied to a metal substrate, preferably a coating composition for rust prevention, and more preferably a coating composition for primary rust prevention.
[0048] 2.Paint composition The modified epoxy resin of the present invention can form a coating film having excellent adhesion durability. Therefore, the present invention also provides a coating composition containing the modified epoxy resin (I) (hereinafter also referred to as "component (I)"). The coating composition of the present invention can be preferably used as an undercoat coating composition.
[0049] 2-1.(I) Modified epoxy resin The modified epoxy resin, which is component (I), is as described above in "1. Modified epoxy resin."
[0050] 2-2.(II) Anti-rust pigments The coating composition of the present invention may contain, in addition to the above-mentioned component (I), an anti-rust pigment (II) (hereinafter also referred to as "component (II)").
[0051] As the (II) component, any component known as an anti-rust pigment can be used without any particular limitation. Specific examples include (II-1) phosphate compounds, (II-2) molybdate compounds, (II-3) zinc salt compounds (provided that they are other than the (II-1) compound and the (II-2) compound), (II-4) alkaline earth metal salt compounds (provided that they are other than the (II-1) compound and the (II-2) compound), and (II-5) bismuth compounds (provided that they are other than the (II-1) compound and the (II-2) compound), and one or more of these can be appropriately selected.
[0052] Examples of the phosphate compound that is the (II-1) compound include phosphites such as zinc phosphite, calcium phosphite, magnesium phosphite, iron phosphite, and aluminum phosphite; phosphates such as zinc phosphate, calcium phosphate, magnesium phosphate, iron phosphate, and aluminum phosphate; and condensed phosphates such as zinc polyphosphate, calcium polyphosphate, magnesium polyphosphate, and aluminum polyphosphate. In particular, examples of aluminum polyphosphate include aluminum dihydrogen tripolyphosphate treated with metal compounds (e.g., chlorides, hydroxides, carbonates, sulfates, etc. of zinc, calcium, magnesium, manganese, bismuth, cobalt, tin, zirconium, titanium, strontium, copper, iron, lithium, aluminum, nickel, and sodium). Commercially available products of phosphites include EXPERT NP-1500, NP-1530, and EXPERT NP-1600 (manufactured by Toho Pigment Co., Ltd.); commercially available products of phosphates, particularly zinc phosphates, include ZP-DL, P-WF, PW-2, D-1, ZP-50S, ZP-SB, ZP-HS, MZP-500, MP-620PMG, and ZP-600 (manufactured by Kikuchi Color Co., Ltd.), and EXPERT NP-530 (manufactured by Toho Pigment Co., Ltd.); commercially available products of condensed phosphates, particularly aluminum polyphosphates, include K-WHITE140, K-WHITE Ca650, K-WHITE#450H, K-WHITE G105, K-WHITE#105, K-WHITE#108, K-WHITE#82, and K-WHITE#84S (manufactured by Teika Co., Ltd.).
[0053] Examples of the molybdate compound (II-2) include calcium molybdate, aluminum molybdate, barium molybdate, molybdenum trioxide, sodium molybdate, and ammonium molybdate. Examples of commercially available products of the molybdate compound, particularly aluminum molybdate, include LF Bosei PM-300c and PM-303W (manufactured by Kikuchi Color Co., Ltd.).
[0054] Examples of the zinc salt compound, which is the compound (II-3), include zinc chloride, zinc oxide, zinc sulfide, zinc sulfate, etc. Commercially available zinc salt compounds include zinc oxide type 1 (manufactured by Sakai Chemical Industry Co., Ltd.), zinc oxide type 3 (manufactured by Honjo Chemical Co., Ltd.), Sachtolich HD (zinc sulfide; trade name; manufactured by Sachleben Chemie GmbH), and zinc chloride (manufactured by Nagai Pharmaceutical Co., Ltd.).
[0055] Examples of the alkaline earth metal salt compound, which is the (II-4) compound, include oxides, hydroxides, silicates, and carbonates of alkaline metals such as calcium, magnesium, and strontium. The alkaline earth metal salt compound may be surface-treated with a surface treatment agent such as a fatty acid, rosin acid, or silane coupling agent. Examples of commercially available alkaline earth metal salt compounds, particularly calcium carbonate, include NS#2300, NS#1000, NS#400, and NS#100 (manufactured by Nitto Funka Kogyo Co., Ltd.), Hakuenka CC, Hakuenka CCR, Hakuenka DD, Vigot 10, Vigot 15, and Hakuenka U (manufactured by Shiraishi Calcium Co., Ltd.).
[0056] Examples of the bismuth compound (II-5) include bismuth oxide, bismuth hydroxide, basic bismuth carbonate, bismuth nitrate, bismuth silicate, and bismuth organic acids.
[0057] The above-mentioned anti-rust pigments may be used alone or in combination of two or more kinds.
[0058] Among the above-mentioned anti-rust pigments, from the viewpoint of improving the adhesion durability of the coating film, preferred are (II-1) compound, (II-3) compound, and / or (II-4) compound, and more preferred are aluminum polyphosphate, zinc oxide, and / or calcium carbonate.
[0059] Among the above-mentioned rust-preventive pigments, from the viewpoint of increasing the adhesion durability of the coating film, it is preferable to use at least the (II-1) compound, and from the viewpoint of increasing the adhesion durability of the coating film against water immersion and / or salt water, it is more preferable to combine the (II-1) compound with the (II-3) compound and / or the (II-4) compound, and from the viewpoint of further increasing the adhesion durability of the coating film against salt water, it is even more preferable to combine the (II-1) compound with the (II-3) compound and the (II-4) compound. In these cases, the (II-1) compound is particularly preferably aluminum polyphosphate, the (II-3) compound is particularly preferably zinc oxide, and the (II-4) compound is particularly preferably calcium carbonate.
[0060] In the coating composition of the present invention, the total amount of component (II) per 100 parts by mass of component (I) is not particularly limited, but from the viewpoint of improving the adhesion durability of the coating film, it is, for example, 25 to 125 parts by mass, preferably 30 to 115 parts by mass, more preferably 45 to 105 parts by mass, even more preferably 60 to 95 parts by mass, and even more preferably 75 to 85 parts by mass.
[0061] 2-3.(III) Epoxy-functional alkoxysilanes From the viewpoint of improving the adhesion durability of the coating film, particularly against salt water, it is preferred that the coating composition of the present invention further contains (III) an epoxy-functional alkoxysilane (hereinafter also referred to as "component (III)") in addition to the above component (I) or in addition to the above components (I) and (II).
[0062] An epoxy-functional alkoxysilane is a compound having an epoxy group and a hydrolyzable silyl group in one molecule. A specific example of an epoxy-functional alkoxysilane is a compound represented by the following formula (2). In the formula, R 1 is a monovalent organic group having a glycidyl group, and R 2 and R 3 each independently represents an alkyl group having 1 to 5 carbon atoms, s represents an integer of 1 to 10, and t represents an integer of 0 to 2.
[0063] [ka]
[0064] More specific examples of the epoxy-functional alkoxysilane represented by (2) above include glycidoxymethyltrimethoxysilane, glycidoxymethyltriethoxysilane, 2-glycidoxyethyltrimethoxysilane, 2-glycidoxyethyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane (GLYMO), 3-glycidoxypropyltriethoxysilane, 4-glycidoxybutyltrimethoxysilane, 4-glycidoxybutyltriethoxysilane, and condensates thereof.
[0065] In the coating composition of the present invention, the amount of component (III) per 100 parts by mass of component (I) is not particularly limited, but from the viewpoint of improving the adhesion durability of the coating film, it can be, for example, more than 0 parts by mass and not more than 24 parts by mass, preferably more than 0 parts by mass and not more than 18 parts by mass, and more preferably more than 0 parts by mass and not more than 12 parts by mass, and from the viewpoint of further improving the adhesion durability of the coating film particularly to salt water, it is even more preferably 4 to 11 parts by mass, even more preferably 7 to 11 parts by mass, and even more preferably 9 to 11 parts by mass.
[0066] 2-4.Other ingredients The coating composition of the present invention may further contain other components in addition to the above-mentioned component (I) and the above-mentioned component (II) and / or component (III) added as necessary, to the extent that they do not adversely affect the rust-preventive performance and adhesion durability. Examples of other components include solvents (similar to the solvents described in the above "1-5. Synthesis of modified epoxy resin"), extender pigments (e.g., talc, aluminum hydroxide, aluminum sulfate, barium sulfate, etc.), white pigments (e.g., titanium oxide, etc.), coloring pigments, plasticizers, pigment dispersants, surface conditioners, defoamers, thickeners, shatterproofing agents, ultraviolet absorbers, etc.
[0067] In the coating composition of the present invention, the content of the solvent is not particularly limited, but may be, for example, 20 to 60 mass %, preferably 30 to 50 mass %, and more preferably 35 to 45 mass %.
[0068] 3.Laminate The coating composition of the present invention can form a coating film having excellent adhesion durability. Specifically, the modified epoxy resin of the present invention has an excellent property of maintaining a state of adhesion to the metal substrate even when the coating film is applied to a metal substrate as a coating film and is subjected to external stimuli such as impact, water immersion, and / or salt water. Therefore, the present invention also provides a laminate comprising a metal substrate and a coating film of the coating composition applied to the metal substrate.
[0069] Examples of the material of the metal substrate include iron, aluminum, stainless steel, etc., but iron, which is inherently prone to corrosion, is particularly preferred because the coating film formed by the coating composition of the present invention has excellent adhesion durability and excellent rust prevention effect. More specific examples of the iron substrate include steel (cold-rolled steel plate, hot-rolled steel plate, high-tensile steel plate, tool steel, alloy tool steel, etc.), cast iron (spheroidized graphite cast iron, gray cast iron, etc.), and surface-treated steel plate (galvanized steel plate, zinc phosphate-treated steel plate, zirconium-treated steel plate, etc.). Examples of the aluminum substrate include Al1085, Al1050, Al1100, Al2017, Al2024, Al3003, Al5052, Al5056, Al5062, Al6061, Al6063, Al7075, etc. Examples of stainless steel substrates include austenitic stainless steel (SUS201, SUS202, SUS301, SUS302, SUS303, SUS304, SUS305, SUS316, SUS317, etc.), martensitic stainless steel (SUS403, SUS420, SUS630, etc.), and ferritic stainless steel (SUS405, SUS430, SUS430LX, etc.).
[0070] The thickness of the coating film of the above coating composition is, for example, 5 to 40 μm, preferably 10 to 38 μm, more preferably 20 to 36 μm, and even more preferably 25 to 32 μm.
[0071] The laminate of the present invention can be produced by a process of coating the above-mentioned coating composition on the surface of a metal substrate to form a coating composition layer, and a process of drying and curing the coating composition layer to form a coating film. The coating method is not particularly limited, and for example, a conventionally known method such as air spray or airless spray can be used. The drying and curing conditions are also not particularly limited, and examples of the conditions include 10 to 150°C, preferably 20 to 100°C, and 5 to 30 minutes, preferably 10 to 20 minutes.
[0072] The laminate of the present invention may have a coating film of the above-mentioned coating composition as an undercoat coating film, and a topcoat coating film may be laminated on the undercoat coating film. The topcoat coating film is not particularly limited, and examples thereof include coating films of topcoats such as two-liquid urethane coating films, melamine baking coating films, acrylic baking coating films, HAA (β-hydroxyalkylamide) curing powder coating films, and blocked isocyanate curing powder coating films.
[0073] The thickness of the topcoat coating film is, for example, 10 to 90 μm, and preferably 20 to 70 μm.
[0074] 4.Goods The laminate described above can be provided in the form of an article having a specific use and / or function, that is, the present invention also provides an article including the laminate described above.
[0075] Examples of the article of the present invention include articles using a metal substrate, such as structures such as ships, marine structures, plants, bridges, and land tanks, vehicles such as automobiles and trains, machine tools, construction machinery, steel furniture, watches, mobile phones, and parts for cameras. EXAMPLES
[0076] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these.
[0077] (1) Material Details of the materials used in the production of the modified epoxy resin-containing resin composition 1 and the resin composition 2 in the examples and comparative examples are as follows.
[0078] (1-1) Modified epoxy resin synthetic material [Table 1]
[0079] (1-2) Materials for coating composition 2 [Table 2]
[0080] In Tables 4A to 7A, the units of the numerical values showing the amounts of component (a1), semi-solid epoxy resin, component (a2), component (b), and component (c) used are "parts by mass," and in Tables 8A to 10A, the units of the numerical values showing the amounts of component (I), component (II), component (III), and other components used are also "parts by mass."
[0081] (1-3) Metal base material SPCC-SD: Cold-rolled steel sheet (manufactured by Nippon Test Panel Co., Ltd.) Zn / Steel plate: Electrogalvanized steel plate (manufactured by Nippon Test Panel Co., Ltd.) ZPO / Steel plate: Zinc phosphate-treated steel plate (manufactured by Nippon Test Panel Co., Ltd.) Zr / Steel plate: Zirconium-treated cold-rolled steel plate (Cold-rolled steel plate was prepared after being zirconium-treated.) Aluminum: Al5052 (TP Giken Co., Ltd.) Stainless steel: SUS304 (manufactured by TP Giken Co., Ltd.)
[0082] (1-4) Topcoat paint of paint composition 2 Two-component urethane paint: White two-component curing urethane paint (product name: Stark (R) 1, Natoco Co., Ltd.) was mixed in the base agent:hardener ratio specified in the catalog, and then appropriately diluted with thinner before use. Melamine baking paint: White melamine resin baking paint (product name: Hi-Merit, Natoco Corporation) was diluted with thinner and used. Acrylic baking paint: White acrylic resin baking paint (product name: Acrylist (R) Hi, Natoco Co., Ltd.) was diluted with thinner and used. HAA curing powder paint: White Primid curing polyester powder paint (product name: Econa (R) 51A, Natoco Co., Ltd.)
[0083] (2) Synthesis of modified epoxy resins I-1 to I-25 (production of coating composition 1) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, the indicated amounts of (a1) component or semi-solid epoxy resin, (a2) component, and (b) component in Tables 4A to 7A, 80 parts by mass of butyl cellosolve, and 90 parts by mass of N-butyl acetate were charged, and the temperature was raised to 110°C while stirring and maintained for 1 hour. Subsequently, 200 parts by mass of glycol ether solvent and the indicated amounts of (c) component in Tables 4A to 7A were added, and the temperature was raised to 125°C and maintained for 5 hours to synthesize modified epoxy resins I-1 to I-25. Thereafter, the reaction liquid was diluted with a mixed solvent of glycol ether solvent and N-butyl acetate (volume ratio 1:1) to obtain a resin composition containing modified epoxy resins I-1 to I-25 at a solid content of 40% by mass (hereinafter referred to as "coating composition 1").
[0084] (3) Preparation of coating composition 2 250 parts by mass of the coating composition 1 obtained in (2) above (100 parts by mass of modified epoxy resins I-1 to I-25), 60 parts by mass of glycol ether solvent, 40 parts by mass of isobutyl acetate, and the (II) component and other components shown in Tables 8A to 10A were stirred and mixed in the indicated amounts to prepare a mixed liquid. The resulting mixed liquid was sealed in a polyethylene container together with titania beads, and dispersed for 2 hours using a paint shaker (manufactured by Asada Iron Works Co., Ltd.) to prepare a dispersion. The resulting dispersion was added with the indicated amounts of the (III) component shown in Tables 8A to 10A and 0.1 parts by mass of a silicon-based surface conditioner (manufactured by BYK-Chemie, BYK-342) to prepare a coating composition 2.
[0085] (4) Coating film performance evaluation of coating composition 1 (4-1) Preparation of test panels As metal substrates, cold-rolled steel sheets (SPCC-SD) and electrogalvanized steel sheets (Zn / steel sheets) were prepared with dimensions of width 75 mm, length 150 mm, and thickness 0.8 mm, and coating composition 1 was applied to the surface of each metal substrate by air spray to a dry film thickness of 30 μm. After that, the coating was dried and cured in an atmosphere at 20° C. for 7 days to obtain each test plate 1 in the form of a laminate including the metal substrate and the coating film of coating composition 1 provided on the metal substrate.
[0086] (4-2) Adhesion durability evaluation (4-2-1) Adhesion durability against impact Using a DuPont impact resistance tester, an impact was applied to the coating surface of each test panel 1 obtained in (4-1) above under the following conditions: weight of 500 g, tip diameter of the shotgun of 1 / 2 inch, drop height of 50 cm. After that, the condition of the coating was observed and evaluated based on the following criteria. This test was carried out under the conditions of a temperature of 23°C and a relative humidity of 50%.
[0087] ◎: No cracks were observed ◯: Very slight cracks occurred, but no peeling of the coating was observed △: Slight cracks were observed, but no peeling of the coating was observed. ×: Cracks were generated and peeling of the coating was observed.
[0088] In addition, in the cases where no peeling was observed, the evaluations of ◎, ◯, and △ were given, it was evaluated that the adhesion durability against impact met the specified standard. Furthermore, among the evaluations of ◎, ◯, and △, in which the adhesion durability against impact was observed according to the specified standard, the crack resistance can be evaluated based on the amount of cracks, and specifically, the crack resistance can be evaluated in the order of ◎, ◯, and △ (◎ being the most excellent). The results are shown in Tables 4A to 7A.
[0089] (4-2-2) Adhesion durability against water immersion Test panel 1 was immersed in 40°C warm water for the indicated time according to the method in accordance with JIS K5600-6-2 "Chemical properties of coating film - Liquid resistance (water immersion method)". After immersion, test panel 1 was removed from the warm water and dried at room temperature for 24 hours. After that, a test based on JIS K5600-5-6 (1999) "Mechanical properties of coating film - Adhesion (cross-cut method)" was conducted, and the adhesion to the substrate was evaluated based on the following two evaluation criteria.
[0090] <Evaluation Criteria 1-JIS K5600-5-6 Adhesion (Cross-Cut Method) Evaluation Criteria> [Table 3]
[0091] According to the evaluation criteria 1, if the evaluation was rated as Class 0, Class 1, or Class 2 (Class 0 being the best), the adhesion durability against water immersion was evaluated as meeting the predetermined criteria. The results are shown in Tables 4A to 7A.
[0092] <Evaluation Criteria 2 - Number of Peels and Edge Chipping> The number of peeled off squares ("peeled number") was counted out of 100 cross-cut squares. The shape of the edge chipping was evaluated according to the following criteria. ◎: No chipping was observed on the edges and / or intersections of the cut lines. ○: Slight chipping was observed on the edges and / or intersections of the cut lines. △: Chips were found on the edges and / or intersections of the cut lines, and slight peeling of the mass was observed. ×: Numerous chips were found at the edges and / or intersections of the cut lines, and peeling of the mass was observed.
[0093] According to evaluation criterion 2, if the number of peelings was 3 or less (the fewer the number of peelings, the better) and the edge chipping was rated as ◎, ◯, or △ (◎ being the best), it was evaluated that the adhesion durability against water immersion met the specified standard. The results are shown in Tables 4A to 7A.
[0094] (4-2-3) Adhesion durability against salt water In the coating film of each test plate 1, two 1 mm-wide cuts were made diagonally across the area about 10 mm inward from the end of the test plate so as to reach the base material (metal substrate) of the test plate 1. Using the test plate with the cuts, a salt spray test was performed for the indicated time in accordance with JIS K5600-7-1 (1999) "Long-term durability of coating film - neutral salt spray resistance". After the salt spray, the test plate was left at room temperature for 3 hours to dry. A 24 mm-wide adhesive tape (industrial cellophane tape manufactured by Nichiban Co., Ltd.) was evenly pressed with the fingertips so as to cover the cut line of the dried test plate, without leaving any air bubbles (care was taken to ensure that the cellophane tape was aligned along the cut line and that the cut line was located in the center of the cellophane tape). Then, the edge of the pressed tape was held and pulled at an angle of 60 degrees to the coating surface to peel the tape off the coating. After removing the tape, the maximum peel width on one side of the coating film from the cut line position (maximum value 12 mm) was measured. If this peel width was 3 mm or less (the smaller the peel width, the better), it was evaluated that the adhesion durability against salt water met the specified standard. The results are shown in Tables 4A to 7A.
[0095] (4-3) Other Adhesion Durability Evaluations Except for changing the metal substrate to zinc phosphate-treated steel plate (ZPO / steel plate), zirconium-treated steel plate (Zr / steel plate), Al5052 (aluminum), or SUS304 (stainless steel), the adhesion durability against water immersion and the adhesion durability against salt water were evaluated in the same manner as in (4-2-2) and (4-2-3) above. The results are shown in Tables 4B to 7B.
[0096] (4-4) Bend resistance evaluation A bending test was conducted in accordance with JIS K5600-5-1 (1999) "Mechanical properties of coating film - Bending resistance (cylindrical mandrel method)" to deform each test plate 1. The test was conducted with a type 1 testing device using a cylindrical mandrel with a diameter of 3 mm. After the test, the coating film condition was visually observed and evaluated based on the following criteria. The results are shown in Tables 4A to 7A.
[0097] ◎: No cracks found in the coating 〇: The coating has very slight cracks △: The coating has cracks
[0098] (5) Coating film performance evaluation of coating composition 2 (5-1) Preparation of test panels Resin composition 2 was applied to the surface of each of a cold-rolled steel plate and an electrolytic galvanized steel plate (width 75 mm, length 150 mm, thickness 0.8 mm) by air spray to a dry film thickness of 30 μm (undercoat coating film). Subsequently, a two-component urethane paint was applied as a topcoat paint and allowed to stand for 7 days in an atmosphere at 20°C (topcoat coating film). As a result, a test plate 2 was obtained in the form of a laminate including a metal substrate, a coating of paint composition 2 provided on the metal substrate (undercoat coating film), and a topcoat coating film provided on the undercoat coating film.
[0099] (5-2) Adhesion durability evaluation For the test panel 2, the adhesion durability against impact, adhesion durability against water immersion, and adhesion durability against salt water were evaluated in the same manner as in (4-2) above. The results are shown in Tables 8A to 10A.
[0100] (5-3) Other Adhesion Durability Evaluations The adhesion durability against water immersion and the adhesion durability against salt water were evaluated in the same manner as in (4-2-2) and (4-2-3) above, except that the metal substrate was changed to zinc phosphate-treated steel plate (ZPO / steel plate), zirconium-treated steel plate (Zr / steel plate), Al5052 (aluminum), or SUS304 (stainless steel), or the topcoat paint was changed to melamine baking paint (baked at 100°C for 20 minutes after painting and then left to stand in a 20°C atmosphere for 3 days to form a coating film), acrylic baking paint (baked at 120°C for 20 minutes after painting and then left to stand in a 20°C atmosphere for 3 days to form a coating film), or HAA curing powder paint (baked at 160°C for 20 minutes after painting with a corona electrostatic coating gun and then left to stand in a 20°C atmosphere for 3 days to form a coating film with a thickness of 60 μm). The results are shown in Tables 8B to 10B.
[0101] [Table 4A]
[0102]
Table 4B
[0103]
Table 5A
[0104]
Table 5B
[0105]
Table 6A
[0106]
Table 6B
[0107]
Table 7A
[0108]
Table 7B
[0109]
Table 8A
[0110]
Table 8B
[0111]
Table 9A
[0112]
Table 9B
[0113] [Table 10A]
[0114]
Table 10B
Claims
1. The epoxy resin has a molecular structure obtained by reacting (a1) a solid epoxy resin, (a2) a liquid epoxy compound, (b) an amine, and (c) a polycarboxylic acid, The modified epoxy resin, wherein the component (a2) is a polyol polyglycidyl ether.
2. 2. The modified epoxy resin according to claim 1, wherein the epoxy equivalent of the component (a1) is 430 or more.
3. 3. The modified epoxy resin according to claim 1, wherein the epoxy equivalent of the component (a2) is 330 or less.
4. The modified epoxy resin according to any one of claims 1 to 3, wherein the amount of the (a2) component is 2 to 180 parts by mass per 100 parts by mass of the (a1) component.
5. The modified epoxy resin according to any one of claims 1 to 4, wherein the component (b) contains a primary amine and a secondary amine.
6. 6. The modified epoxy resin of claim 5, wherein the primary amine is an aliphatic amine.
7. The modified epoxy resin according to claim 6, wherein the aliphatic amine has 8 or more carbon atoms.
8. The epoxy resin has a molecular structure obtained by reacting (a1) a solid epoxy resin, (a2) a liquid epoxy compound, (b) an amine, and (c) a polycarboxylic acid, The component (b) contains a primary amine and a secondary amine, The modified epoxy resin, wherein the primary amine is an aliphatic amine having 8 or more carbon atoms.
9. The modified epoxy resin according to claim 8, wherein the epoxy equivalent of the component (a1) is 430 or more.
10. The modified epoxy resin according to claim 8 or 9, wherein the epoxy equivalent of the component (a2) is 330 or less.
11. The modified epoxy resin according to any one of claims 8 to 10, wherein the component (a2) is a bisphenol type epoxy resin.
12. The modified epoxy resin according to any one of claims 8 to 11, wherein the amount of the (a2) component is 2 to 180 parts by mass per 100 parts by mass of the (a1) component.
13. The modified epoxy resin according to any one of claims 5 to 12, wherein a molar ratio of the secondary amine to the primary amine is 0.3 to 10.
14. The modified epoxy resin according to any one of claims 1 to 13, wherein the component (c) is an aliphatic polycarboxylic acid.
15. The modified epoxy resin according to claim 14, wherein the aliphatic polycarboxylic acid has 8 or more carbon atoms.
16. The modified epoxy resin according to any one of claims 1 to 15, wherein the molar ratio of amino group hydrogen atoms to epoxy groups is 0.2 or more.
17. The modified epoxy resin according to any one of claims 1 to 16, wherein the molar ratio of carboxyl groups to epoxy groups is 0.8 or less.
18. A coating composition comprising the modified epoxy resin (I) according to any one of claims 1 to 17.
19. The coating composition according to claim 18, further comprising (II) an anti-rust pigment.
20. 20. The coating composition according to claim 19, wherein the component (II) is selected from the group consisting of a phosphate compound, a molybdate compound, and a zinc salt compound, an alkaline earth metal salt compound, and a bismuth compound other than the phosphate compound and the molybdate compound.
21. The coating composition according to claim 18 or 19, wherein the blending amount of the component (II) is 25 to 125 parts by mass per 100 parts by mass of the component (I).
22. The coating composition according to any one of claims 18 to 21, further comprising (III) an epoxy-functional alkoxysilane.
23. The coating composition according to claim 22, wherein the blending amount of the component (III) is more than 0 parts by mass and not more than 24 parts by mass per 100 parts by mass of the component (I).
24. A laminate comprising a metal substrate and a coating film of the coating composition according to any one of claims 18 to 23 provided on the metal substrate.
25. 25. The laminate according to claim 24, wherein the material of the metal substrate is selected from the group consisting of iron, aluminum, and stainless steel.
26. 26. An article comprising the laminate of claim 24 or 25.
Citation Information
Patent Citations
Cationic electrodeposition coating composition
JP1994157950A
Modified epoxy resin
JP1999100431A
Binder and composition for coating
JP2001164180A
Epoxy resin composition and epoxy resin emulsion
JP2004149696A
Modified epoxy resin composition
JP2004204135A